An investigation into syntactic and semantic features of hyperbole in english and vietnamese love songs - Trương,Hoài Uyên. (ĐHNN, 2016)
The thesis aims to investigate, describe and analyze syntactic and semantic features of hyperbole in English and Vietnamese love songs. In order to conduct the study, the descriptive analysis with the combination of both qualitative and quantitative research methods is adopted on the basis of the theories of hyperbole by Galperin (1981) and Clardige (2011). The data are instances of hyperbole extracted from English love songs and Vietnamese love songs. English samples and Vietnamese samples of hyperbole are collected in such grammatical forms as phrases, clauses and sentences. The study findings reveal that hyperbole is frequently employed in English and Vietnamese love songs with some differences and similarities from semantic and syntactic perspectives. On the basis of the findings, some implications and suggestions on comprehending, translating the language of hypeprbole as well as learning and teaching English through stylistics in general and hyperbole in particular are put forward.
Keywords: syntactic and semantic, features of hyperbole